Understanding sexual harassment experience among undergraduate students’ in higher education institution in Malaysia / Siti Rapidah Omar Ali ... [et al.] - Omar Ali, Siti Rapidah; Mohd Said, Nur Shafini; Mat, Khalid Amin; Mat Zali, Masliza; Aziz, Nurulnadwan (2017)
This study is conducted to gain an understanding of the issue of sexual harassment in the academic setting. Specifically, the objectives of this study are to examine the awareness of sexual harassment experienced among students, identify the effects of sexual harassment and the risk factor contributed to the act. A modified self-administered questionnaires designed by the DEOC Task Force on Discrimination and Sexual Harassment, USA was used as the main data collection instrument in this study. The questionnaires were distributed to Bachelor Degree and Diploma students from all faculties in Universiti Teknologi MARA Terengganu (Dungun, Bukit Besi and Kuala Terengganu campus). This study applied stratified random sampling. Data was analyzed using descriptive statistics such as mean, frequency and percentage. It is expected through the findings obtain from this study, the need for having proper policy or sexual harassment safety guidelines for students, lecturers and other academic staffs could be identified in order to protect themselves from the incident anytime and anywhere.